Chapter 12 - Modelling the effects of climate change in estuarine ecosystems with coupled hydrodynamic and biogeochemical models - Rodrigues, Marta (2020)
Estuaries are among the most productive ecosystems on Earth and provide multiple ecosystem services. They harbor ecologically important habitats for fish, shellfish, and birds and support diverse human activities (e.g., marine transportation, fishing, and tourism). However, climate change, together with the predicted increase of human activities, may increase the hazards in these systems and alter estuarine ecosystems dynamics. Coupled hydrodynamics and biogeochemical numerical models, which jointly simulate the physical, chemical, and biological processes at the relevant spatial and temporal scales, are useful tools to support climate change impact studies on estuarine ecosystems dynamics. A general overview of some well-established coupled hydrodynamic–biogeochemical models is presented and their use to support the study of climate change impacts on estuarine ecosystems is discussed. The use of coupled hydrodynamic–biogeochemical models to support the long-term, climate-adapt management of estuarine ecosystems and the definition of mitigation and adaptation strategies within a climate change context is demonstrated with a case study: the evaluation of climate change impacts in the lower trophic levels dynamics in the Aveiro lagoon using the model ECO-SELFE. Existing coupled hydrodynamic–biogeochemical models already have numerous benefits in climate change impact studies. Future research should improve these models’ capabilities to reduce limitations and uncertainties, in particular those related to the coupled representation of the physical and biological processes and their feedbacks over long time scales.